An Algorithm for Color-Based Password Authentication to Increase Security Level - Selamat, Siti Rahayu; Cai, Soung Young; Hassan, Nor Hafeizah; Yusof, Robiah (Department of Informatics, Siliwangi University, Indonesia, 2024)
Security level in authentication is essential to decrease the possibility of an account being guessed. Several authentication methods are widely used nowadays, covering digital aspects such as passwords, challenge-response, public and private key / digital certificates, and physical elements such as fingerprints, iris, or retina scanning. This paper aims to focus on solving the problem of the password. This textual authentication consists of many vulnerabilities open to attacks like eavesdropping, dictionary attack, and brute force attack by increasing the level of complexity in the authentication algorithm. In this paper, we proposed a new color-based password authentication algorithm to solve the vulnerabilities in textual authentication. The color-based password authentication algorithm consists of three main processes: color selection, hexadecimal password encryption, and password verification. This research contributes to a new color-based authentication by increasing the complexity of the verification process that can solve the vulnerabilities of textual authentication and harden the level of security in the authentication layer. This color-based authentication algorithm could fully replace textual authentication in the future and is worth using in sensitive data domains such as medical and health or banking institutions.